2021
DOI: 10.1186/s41118-021-00125-7
|View full text |Cite
|
Sign up to set email alerts
|

Adult death registration in Matlab, rural Bangladesh: completeness, correlates, and obstacles

Abstract: Civil registration of vital events such as deaths and births is a key part of the process of securing rights and benefits for individuals worldwide. It also enables the production of vital statistics for local planning of social services. In many low- and lower-middle-income countries, however, civil registration and vital statistics (CRVS) systems do not adequately register significant numbers of births and, especially, deaths. In this study, we aim to estimate the completeness of adult death registration (fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…They find that underregistration of deaths is mostly associated with household-level poverty, low educational attainment, and higher population density per civil registration center. In contrast to earlier assessments that documented notable subnational sex differentials in death registration completeness in Ecuador, Morocco, and Bangladesh (Haider et al, 2021 ; Peralta et al, 2019 ; Silva, 2016 ;), their findings are more consistent with Castanheira and Monteiro da Silva ( 2022 ) and Adair et al ( 2021 ), who document the non-existence of sex differentials in Peru and several other countries.…”
Section: Applications Of Demographic and Analytical Methods To The St...contrasting
confidence: 67%
See 3 more Smart Citations
“…They find that underregistration of deaths is mostly associated with household-level poverty, low educational attainment, and higher population density per civil registration center. In contrast to earlier assessments that documented notable subnational sex differentials in death registration completeness in Ecuador, Morocco, and Bangladesh (Haider et al, 2021 ; Peralta et al, 2019 ; Silva, 2016 ;), their findings are more consistent with Castanheira and Monteiro da Silva ( 2022 ) and Adair et al ( 2021 ), who document the non-existence of sex differentials in Peru and several other countries.…”
Section: Applications Of Demographic and Analytical Methods To The St...contrasting
confidence: 67%
“…In the seventh paper of the thematic series, Haider et al ( 2021 ) explore the level and determinants of death registration in a rural area of Bangladesh—a country with historically low birth and death registration completeness (United Nations, 2021 ). In their study of the levels and determinants of death registration in rural Bangladesh, the authors found only 1 in 6 adult deaths were registered in a recent 3-year period.…”
Section: Applications Of Demographic and Analytical Methods To The St...mentioning
confidence: 99%
See 2 more Smart Citations
“…In both study groups, the consent scripts included similar explanations of how phone numbers were selected, and statements about that the interview would take approximately 15 minutes to complete. Consent scripts in both groups also mentioned that participants would receive a small amount of airtime (1,200 Malawian Kwachas, or 1.5 US Dollar) as a token of appreciation upon completion of the interview. Since the main themes of the interview differed between treatment and control groups, the description of other study procedures included differed between the two groups (see supporting documents).…”
Section: Methodsmentioning
confidence: 99%